Recognition of social health: A conceptual framework in the context of dementia research - Vernooij-Dassen, Myrra; Verspoor, Eline; Samtani, Suraj; Sachdev, Perminder S.; Ikram, M. Arfan; Vernooij, Meike W.; Hubers, Claudia; Chattat, Rabih; Lenart-Bugla, Marta; Rymaszewska, Joanna; Szczesniak, Dorota; Brodaty, Henry; et al. (Frontiers in Psychiatry, 2022)
ABSTRACT OBJECTIVE The recognition of dementia as a multifactorial disorder encourages the exploration of new pathways to understand its origins. Social health might play a role in cognitive decline and dementia, but conceptual clarity is lacking and hinders investigation of associations and mechanisms. The objective is to develop a conceptual framework for social health to advance conceptual clarity in future studies. PROCESS We use the following steps: underpinning for concept advancement, concept advancement by the development of a conceptual model, and exploration of its potential feasibility. Consensus on the conceptual model has been reached in an iterative process within the international multidisciplinary SHARED study. CONCEPTUAL FRAMEWORK The underpinning consists of a synthesis of epidemiological, theoretical and conceptual resources, which led to define social health as well-being relying on the impact of capacities of the individual and the social environment. Consequently, domains in the conceptual framework are on the individual (e.g.social participation) and the social environmental level (e.g. social network). We hypothesize social health being the driver for using cognitive reserve that slows cognitive impairment or maintains cognitive functioning. The feasibility of the conceptual framework has been demonstrated by its use in guiding the identification and structuring of social health markers within the SHARED study. DISCUSSION The conceptual framework provides guidance for future research and facilitates the identification of modifiable risks and protective factors, which may in turn shape new avenues for preventive interventions. We highlight the paradigm of social health in dementia as a priority for dementia research.